The impact of the Tragist model on the collection of Arabic grammar among female students Intermediate first grade (Journal of the College of Basic Education, 2022)
The current research aims to identify (the effect of the Tragist model on the collection of Arabic grammar among first-grade female students).The current research is determined by a sample of intermediate first-grade students in intermediate and secondary day schools affiliated to the General Directorate of Education of Rusafa / the second in Baghdad Governorate, and the topics of the Arabic grammar book to be taught to intermediate first-grade students in Iraq for the first semester of the year 2012-2013 AD.The researcher followed the experimental design with partial control as a research design, and the research community consisted of secondary and intermediate day schools for girls in the General Directorate of Education of Rusafa / the second in Baghdad.